Wind tunnel experiments of a newly developed two-bladed Savonius-style wind turbine - Roy, Sukanta; Saha, U. (Elsevier, 2015)
Wind tunnel experiments have been conducted with a newly developed two-bladed Savonius-style wind turbine specifically meant for a small-scale energy conversion. This novel shape of the turbine blade is evolved from a series of experiments with different types of blades in the recent past. The developed two-bladed turbine is tested in an open type test section and its performance is assessed in terms of power and torque coefficients. Experiments have also been conducted with other standard blades such as semi-circular, semi-elliptic, Benesh and Bach types in order to have a direct comparison. In this study, all the reported experimental data are inclusive of wind tunnel blockage corrections. Further, the effects of Reynolds number on the dynamic and static characteristics are also discussed. The present investigation demonstrates a gain of 34.8% in maximum power coefficient with the newly developed two-bladed turbine.